PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS "MACROMEDIA FLASH" PADA PEMBELAJARAN TEMATIK KELAS IV TEMA 6 SUB TEMA 1 AKU DAN CITA-CITAKU - Antonius Edy Setyawan; Warkintin Warkintin; Y. Januariko (JUTECH : Journal Education and Technology, 2020)
ABSTRACTThe purpose of this research are to find out the development procedure which is conducted by the researcher on learning media based on macromedia flash 8 in class IV elementary school . This ressearch development is arranged based on the deveopmental stages by Luther, which is has 6 stages, namely (1) Concept (2) design (3) Material collecting (4) Assembly (5) Testing (6) Distribution. The data gathering tools that used are, media expert validation sheets, material expert validation sheets, and students response questionnaire sheets. Learning activity in the classroom are using macromedia flash 8 learning media, teacher lectures, and interactions with students.The  results of  media validators are 83%, categorized as “good” results, the results of material validators are 86%, categorized as “very good”. The results of  student’s questionnarie respose in beta test are 82%, categorized as “good”. Therefore it could be concluded the Development of Learning Media Based on Macromedia Flash on Thematic Learning Class IV Theme 6 Subtheme 1 Me and My Ideals are proper to use.Keywords: Development, Learning Media, Macromedia FlashABSTRAKTujuan penelitian ini adalah untuk mengetahui bagaimana kelayakan media pembelajaran berbasis Macromedia Flash 8 di kelas IV Sekolah Dasar. Penelitian pengembangan ini disusun berdasarkan langkah pengembangan dari Luther, dimana terdapat 6 tahap, yaitu: (1) concept,  (2) design, (3) material collecting, (4) assembly, (5) testing, dan (6) distribution. Pengumpulan data menggunakan lembar angket dan dokumentasi. Alat pengumpul data berupa lembar validasi ahli media, lembar validasi ahli materi, dan lembar angket respon siswa. Kegiatan pembelajaran di kelas menggunakan media pembelajaran berbasis macromedia  flash 8, ceramah guru dan interaksi dengan siswa. Hasil  validasi ahli media sebesar  83%, berkategori “baik”, hasil validasi ahli materi sebesar 86%, berkategori “sangat baik”. Hasil angket tanggapan siswa di sekolah adalah 82% berkategori “baik”. Dengan demikian dapat disimpulkan bahwa Pengembangan Media Pembelajaran Berbasis Macromedia Flash  Pada Pembelajaran  Tematik Kelas IV Tema 6 Sub Tema 1 Aku Dan Cita-Citaku dinyatakan layak digunakan.Kata Kunci: Pengembangan, Media Pembelajaran, Macromedia Flash